Multipurpose zero watermarking algorithm for medical image based on SVD and SAE - Jieli SUN; Yanxia ZHAO; Zenghui ZHOU; Sheng XING (Dianxin kexue)
A multipurpose zero watermarking algorithm was proposed according to the copyright protection and tamper location of medical image.The two information matrices were executed the XOR operation with the original robust watermarking image and the original semi-fragile watermarking image separately to generate zero robust watermarking image and zero semi-fragile watermarking image.The experimental results show that effects of extracted zero watermarking image are terrific,and the algorithm can resist the common attacks,particularly its resistance is effect ive for strong attacks.